The Diagnostic Utility of Transthoracic Echocardiography for the Diagnosis of Infective Endocarditis in the Real World of the Italian Registry on Infective Endocarditis. Issue 8 (12th March 2013) - Cecchi, Enrico; Chirillo, Fabio; Faggiano, Pompilio; Imazio, Massimo; Cecconi, Moreno; Moreo, Antonella; Cialfi, Alessandro; Rinaldi, Mauro; Ponte, Stefano Del; Squeri, Angelo; Gaddi, Oscar; Enia, Francesco; et al.
<x xml:space="preserve">Abstract</x> Background The choice of the imaging modality (transthoracic [TTE] vs. transesophageal echocardiography [TEE]) for the diagnosis of infective endocarditis (IE) depends on different variables. Aim of the present study is to provide updated data on the diagnostic sensitivity and the clinical usefulness of TTE vs. TEE from the Italian Registry on IE (RIEI). Methods The RIEI has enrolled consecutive cases of IE in every participating centre, evaluating diagnostic and therapeutic data from a real world practice perspective. Results From July 2007 to October 2010, 658 consecutive cases with definite IE according to Duke criteria have been enrolled in the RIEI (483 males). The following diagnostic echocardiographic exams were performed: 616 TTE (94%) and 476 TEE (72%). A positive TTE was recorded in 399 cases (65%), an uncertain TTE in 108 cases (17%), and a negative TTE in 109 cases (18%). For TEE, a positive study was reported in 451 cases (95%), uncertain in 13 cases (2.7%), and negative in 12 cases (2.5%) (P < 0.001). This difference is not evident in patients with tricuspid valve IE or i.v. drug addiction, and in Streptococcus bovis or Streptococcus viridans IE. TTE was significantly more performed before the admission and earlier than TEE during admission (P = 0.000). TTE was mainly responsible for the initial diagnosis in 59%. TEE contributed to changing the therapeutic approach in 42%. Conclusions In the real world, TTE is performed earlier and more commonly, and it is the major echocardiographic tool for the initial diagnosis. TEE confirms its superior diagnostic sensitivity in most cases, although it is relatively underused.